Produção de compostos fenólicos a partir de células imobilizadas do líquen Parmotrema andinum (Müll. Arg.) Hale e avaliação de atividade antimicrobiana - NÓBREGA, Nadejda de Azevedo (2015)
Hale and evaluation of antimicrobial activity). Secondary metabolites obtained from lichens should be carefully used by the pharmaceutical, cosmetic, textile and food industries because the extraction and isolation of these metabolites requires large amounts of biomass, which is not renewable due to how slow lichens grow. Nowadays, it is possible to obtain these substances either by tissue culture or cell and enzymatic immobilizations, from an in natura thallus, using a small amount of lichenous material. Therefore, this work aimed to investigate the production of phenolic compounds from Parmotrema andinum (Müll. Arg.) Hale immobilized cells, using sodium acetate as a precursor in the biosynthesis of phenols. Testing of antimicrobial activity with organic extracts of the in natura thallus, cell eluate and lecanoric acid isolated from P. andinum Hale showed antimicrobial activity against Gram-positive bacteria. Through biochromatographic assays, it was possible to associate the antibacterial activity to the lecanoric acid and to another unidentified substance. The substances produced by cell immobilization did not exhibit any inhibitory action against tested microorganisms.